Advokasi dan Tantangan Organisasi Masyarakat Sipil dalam Pembangunan PLTU 3 dan 4 di Nagan Raya - Aminah, Aminah; Hasan, Effendi; Muliadi, Mus; Ubaidullah, Ubaidullah (Sociology Department Of Syiah Kuala University, 2024)
This study examines the role of Civil Society Organizations (CSOs) in responding to the development of Coal-Fired Power Plants (PLTU) 3 and 4 in Nagan Raya Regency, delineating the dynamics between CSOs and the government in the context of energy infrastructure development. Utilizing a descriptive qualitative methodology, this research identifies the social changes and tensions caused by the construction of the power plants, which include increased respiratory disease cases and environmental degradation. The findings indicate that the development of PLTU 3 and 4 has triggered 'Structural Strain' leading to collective community movements, including protests and demands for compensation. Meanwhile, CSOs such as APEL Nagan Raya and YARA Nagan Raya have played significant roles in advocating for environmental and anti-corruption issues. However, the effectiveness of the social movements they initiated remains limited due to the inadequate direct involvement of the impacted community. This study highlights the importance of local leadership and CSOs in addressing the adverse impacts of large-scale infrastructure developments and underscores the necessity of enhancing CSO capabilities and community participation in the development process to ensure sustainable and inclusive growth.AbstrakPenelitian ini mengkaji peran Organisasi Masyarakat Sipil (OMS) dalam menanggapi pembangunan Pembangkit Listrik Tenaga Uap (PLTU) 3 dan 4 di Kabupaten Nagan Raya, memaparkan dinamika antara OMS dan pemerintah dalam konteks pembangunan infrastruktur energi. Melalui metode kualitatif deskriptif, penelitian ini mengidentifikasi perubahan sosial dan ketegangan yang ditimbulkan oleh pembangunan PLTU, termasuk peningkatan kasus penyakit pernapasan dan kerusakan lingkungan. Hasil menunjukkan bahwa pembangunan PLTU 3 dan 4 memicu 'Structural Strain' yang menghasilkan gerakan kolektif masyarakat, termasuk protes dan tuntutan kompensasi. Sementara itu, OMS seperti APEL Nagan Raya dan YARA Nagan Raya berperan penting dalam mengadvokasi isu lingkungan dan korupsi, namun efektivitas gerakan sosial yang mereka inisiasi masih terbatas karena kurangnya keterlibatan langsung masyarakat yang terdampak. Penelitian ini menekankan pentingnya peran kepemimpinan lokal dan OMS dalam menangani dampak negatif pembangunan infrastruktur skala besar, serta pentingnya meningkatkan kapasitas OMS dan partisipasi masyarakat dalam proses pembangunan untuk memastikan pertumbuhan yang berkelanjutan dan inklusif.